The Inner Structure of Lampung Song Lyrics - Hilal, Iqbal; Anantama, Muharsyam Dwi; Gustira, Yinda Dwi (Jayapangus Press, 2025)
The lyrics of a song can be a reflection of society's life because lyrics often contain stories or narratives that are drawn from everyday life. Furthermore, song lyrics can also influence and shape the perceptions and behaviors of society. In this research, the inner structure found in the lyrics of the songs